Binding of Trypanosoma congolense to the walls of small blood vessels - Banks, K.L. (Wiley, 1978)
SYNOPSIS The mesenteric microvasculature was studied in rats and rabbits infected with Trypanosoma congolense. By examining vessels in the living animals, trypanosomes were observed to adhere to vessel walls by their anterior ends. It was evident from stained preparations of the vessels that the microcirculation contained 4–1400 times as many trypanosomes as were free in the cardiac blood. Parasites were more numerous in very small vessels than in larger vessels, and they were clustered in groups within the small vessels. The localization of T. congolense in the microvasculature is demonstrated and it is shown that this localization is established by attachment of the organism to the vessel wall.